The impact of real oil price on real effective exchange rate: The case of Azerbaijan - Fakhri Hasanov (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Using quarterly data from 2000-2007 and applying Error Correction Model and Johansen Co-integration Approaches I estimate the impact of real oil price on the real exchange rate of Azerbaijani manat. Estimation outputs derived from these approaches are very close to each other and indicate that real oil price has statistically significant positive impact on real exchange rate in the long-run. Besides, revealed that relative price as a proxy for productivity has also explanatory power in explaining long-run behavior of real exchange rate. Estimated Error Correction Term indicates that half-life of adjustment toward long-run equilibrium level takes 3-4 quarters. Since findings of this study occur as results of high fiscal expansion my policy suggestions mainly related to Fiscal policy implementations.
Keywords: F31; F41; C32; P24; Q43; 330; Real effective exchange rate; Real oil price; Relative productivity; Azerbaijani manat; Dutch Disease; Oil-exporting Countries; Johansen Co-integration Approach; Error Correction Modeling; Half-life Speed; Ölpreis; Kaufkraftparität; Dutch Disease; Aserbaidschan